Problematika Undang-Undang Kesejahteraan Ibu dan Anak: Kesenjangan Regulasi dan Implementasi - Cristiana, Edelweisia (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
Law Number 4 of 2024 on the Welfare of Mothers and Children reflects the state’s commitment to ensuring the protection of maternal and child rights, particularly during the first 1,000 days of life. However, its implementation faces various challenges, including regulatory inconsistencies with the Manpower Act and weak enforcement mechanisms at the operational level. This article aims to examine the gap between legal norms and practical implementation, as well as to assess the extent to which Law Number 4 of 2024 fills the existing legal vacuum in the protection of mothers and children in Indonesia. This study employs a normative juridical approach with qualitative analysis of relevant legislation and supporting documents. The findings indicate that the effectiveness of protection for working mothers and children depends significantly on intersectoral policy coordination, regulatory harmonization, and institutional capacity strengthening. Without concrete steps in policy integration and legal enforcement, the objectives of the law risk being unfulfilled. Therefore, comprehensive reform in implementation is necessary to ensure the law’s alignment with the state’s constitutional obligation to uphold the welfare of mothers and children. Keywords: Welfare of Mothers and Children, Law Number 4 of 2024, Worker Protection, Policy Synergy, Legal Implementation